New 3D-Culture Approaches to Study Interactions of Bone Marrow Adipocytes with Metastatic Prostate Cancer Cells - Herroon, Mackenzie Katheryn; Diedrich, Jonathan Driscoll; Podgorski, Izabela (Frontiers in Endocrinology, 2016)
Adipocytes are a major component of the bone marrow that can critically affect metastatic progression in bone. Understanding how the marrow fat cells influence growth, behavior and survival of tumor cells requires utilization of in vitro cell systems that can closely mimic the physiological microenvironment. Herein, we present two new 3D culture approaches to study adipocyte-tumor cell interactions in vitro. The first is a transwell-based system composed of the marrow-derived adipocytes in 3D collagen I gels and reconstituted basement membrane-overlayed prostate tumor cell spheroids. Tumor cells cultured under these 3D conditions are continuously exposed to adipocyte-derived factors and their response can be evaluated by morphological and immunohistochemical analyses. We show via immunofluorescence analysis of metabolism-associated proteins that under 3D conditions tumor cells have significantly different metabolic response to adipocytes than tumor cells grown in 2D culture. We also demonstrate that this model allows for incorporation of other cell types, such as bone marrow macrophages, and utilization of di-quenched collagen substrates for examination of proteolysis-driven responses to adipocyte-and macrophage-derived factors. Our second 3D culture system is designed to study tumor cell invasion towards the adipocytes and the consequent interaction between the two cell types. In this model, marrow adipocytes are separated from the fluorescently labeled tumor cells by a layer of collagen I. At designated time points adipocytes are stained with BODIPY and confocal z-stacks are taken through the depth of entire culture to determine the distance travelled between the two cell types over time. We demonstrate that this system can be utilized to study effects of candidate factors on tumor invasion towards the adipocytes. We also show that immunohistochemical analyses can be performed to evaluate the impact of direct interaction of prostate tumor cells with adipocytes. Our models underline the importance of using the appropriate culture conditions to mimic physiological interactions between marrow adipocytes and metastatic tumor cells. These systems have a potential to be utilized for analyses of various factors that may be regulated by the adipocytes in bone. Their application likely extends beyond metastatic prostate cancer to other tumors that colonize bone marrow microenvironment.